Review Artikel: Memperbaiki Permeabilitas Obat Bcs Kelas II, III Dan IV Dengan Metode Ko-Amorf - Vicania Raisa Rahman; Arif Budiman (Journal of Pharmaceutical and Sciences, 2023)
Drugs in the co-amorphous form are combinations of amorphous drugs with co-formers that have good solubility and stability so that dissolution becomes better and influences the therapeutic effect of drugs better, too the first time a co-amorphous formulation was made to overcome the low solubility of BCS class II. However, the current study found that co-amorphous formulations could improve solubility and the permeability of BCS class III and IV drugs. Co-amorphous production methods include cryo-milling, melting and quench cooling, solvent evaporation, and spray drying. This article review was conducted to gather information about BCS class II, III, and IV drugs made in co-amorphous forms to improve the physicochemical properties of drugs, such as solubility, permeability, and stability. Articles were collected from 20 research journals published over the last ten years. The co-amorphous drug testing of 10 drugs showed higher solubility and permeability than in crystal form